RISK FACTORS FOR HEAT RELATED DEATHS DURING THE JUNE 2015 HEAT WAVE IN KARACHI, PAKISTAN - Saleem, Syed Ghazanfar; Ansari, Tehreem; Ali, Ashraf Shamshad; Fatima, Sara; Rizvi, Mariam Hassan; Samad, Muhammad Abdul (Journal of Ayub Medical College Abbottabad, 2017)
Background: Mortality as a consequence of heat related illness is a public health concern. Emergency department (ED) experiences increased patients’ flow and decreased survival as a consequence of heat stroke during the episodes of heat wave. The present study was conducted to identify the risk factors for mortality among victims of heat wave (17th - 23rd June), 2015 evaluated in the Emergency Department of The Indus Hospital (TIH), Karachi. Methods: In this cross-sectional study data was retrospectively collected. Out of 2278 patients, 150 patients who satisfied the inclusion criteria (core body temperature >38 °C, dehydrated and CNS dysfunction without infection) were included. Data was analysed using SPSS version 21 (IBM). Results: Among 150 patients included for analysis, the mortality was observed in twenty-four patients (16%). Majority (64.7%) of the patients included in this retrospective study were males and older with median age of 51.5 years. It was identified that non-survivors had significantly lower diastolic blood pressure and oxygen saturation compared to survivors along with higher median reparatory rate, pulse rate, temperature, and length of stay in emergency, shock index, and proportion of unconscious level. Conclusion: The study concluded that heat stroke patients with decreased diastolic blood pressure and oxygen saturation as well as patients with increased shock index, low conscious level and higher core temperature, respiratory and pulse rate should be considered for more intensive management in Intensive Care Unit (ICU) to decrease mortality rate during future heat stroke episodes. Keywords: Emergency department; heat stroke; heat wave; hyperthermia; mortality; Pakistan; Karachi